2024
DOI: 10.2174/1570159x21666230314143803
|View full text |Cite
|
Sign up to set email alerts
|

Physical Exercise to Redynamize Interoception in Substance use Disorders

Abstract: Physical exercise is considered a promising medication-free and cost-effective adjunct treatment for substance use disorders (SUD). Nevertheless, evidence regarding the effectiveness of these interventions is currently limited, thereby signaling the need to better understand the mechanisms underlying their impact on SUD, in order to reframe and optimize them. Here we advance that physical exercise could be re-conceptualized as an “interoception booster”, namely as a way to help people with SUD to better decode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 228 publications
0
4
0
Order By: Relevance
“…Exercise also redirects the mind's attention from psychologically deteriorative thoughts towards connectedness and the curiosity of physical sensations. This phenomenon strengthens a platform for self-evaluation and is also tied to increased healthier choices, sense of purpose, self-efficacy, cognition, self-worth and the ability to better cope with external factors and circumstance as well as decreased loneliness, distraction and perseveration on unhelpful thoughts [37 ▪▪ ,47 ▪ ,53 ▪ ,59 ▪▪ ,60–62,63 ▪▪ ,64–66].…”
Section: Physical Activty: Muscle a Vital Unifying Path For Holistic ...mentioning
confidence: 97%
See 2 more Smart Citations
“…Exercise also redirects the mind's attention from psychologically deteriorative thoughts towards connectedness and the curiosity of physical sensations. This phenomenon strengthens a platform for self-evaluation and is also tied to increased healthier choices, sense of purpose, self-efficacy, cognition, self-worth and the ability to better cope with external factors and circumstance as well as decreased loneliness, distraction and perseveration on unhelpful thoughts [37 ▪▪ ,47 ▪ ,53 ▪ ,59 ▪▪ ,60–62,63 ▪▪ ,64–66].…”
Section: Physical Activty: Muscle a Vital Unifying Path For Holistic ...mentioning
confidence: 97%
“…In addition to muscle appearing to act as a system-wide endocrine organ, exercise is an embodiment practice that provides opportunities to strengthen self-regulatory avenues that benefit neurocognitive, psychological and physical function with an impact on long and short-term global health outcomes. Exercise, as a conscious or unconscious, mindfulness practice may be one of the most comprehensive avenues to enhance intero-/extero/proprioception, which constitutively re-dynamizes one's interactive awareness and responsive adaptation with self, other and our surroundings [59 ▪▪ ,60,61].…”
Section: Physical Activty: Muscle a Vital Unifying Path For Holistic ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its involvement in homeostatic control and conscious interoception (Craig, 2002(Craig, , 2009, the insular cortex constitutes a "gating system" in the dynamic interplay between neurocognitive processes (Droutman et al, 2015a(Droutman et al, , 2015bMolnar-Szakacs & Uddin, 2022;Zhao et al, 2023). fMRI studies have already allowed us to specify how the insula interacts with other brain regions to regulate physical efforts (for a review, see Brevers et al, 2024). For example, Hilty and colleagues (2011) observed that connectivity between the insula and the primary motor cortex increased from the beginning to the end of a cycling exercise.…”
Section: Introductionmentioning
confidence: 99%